Theoretical estimation of efficiency defect in Vapour Compression Refrigeration system using R1234yf, R134a and R1234ze - Soni Shubham; Mishra Punit; Maheshwari Govind; Verma Devendra S (E3S Web of Conferences, 2021)
In presented work, researchers have used efficiency defect as a tool for checking the utility of different refrigerants in Vapour compression refrigeration system. A mathematical model of simple Vapour compression refrigeration system is created. Using first law analysis and exergy analysis efficiency defect is calculated for various components of the system individually and whole vapour compression refrigeration system as well. It is found that R1234yf has highest value of efficiency defect for whole system, whereas R134a has least value of efficiency defect for whole system. Variation of efficiency defect of various components with evaporator temperature is also presented as graphs.